معايير للتحقق من الدقة الهندسية للتصحيح الهندسي للصور الفضائية - عمر الخليل (Tishreen University, 2017)
يعتبر التصحيح الهندسي للصور الفضائية مسألةً أساسيةً في صناعة الخرائط الرقمية وتحديثها, في دمج البيانات متعددة المصادر وفي الإدارة والتحليل في العديد من تطبيقات الجيوماتيك. هذا وتعتبر كثيرات الحدود ثنائية البعد, أكثر التوابع الرياضية انتشاراً في إجراء هذا التصحيح. لقد بيّنت أبحاث سابقة أنّ تطبيق كثيرات الحدود ثنائية البعد مشروط باستوائية الأرض وبالتوزع الموحد لنقاط الضبط ولكنها لم تناقش بشكل واضح معايير الحكم على نجاح أو فشل تطبيقها. سنحاول في هذه الدراسة إعطاء بعض من هذه المعايير وسنحاول تطوير بعض القواعد الكارتوغرافية التشابهية القديمة بحيث تناسب الطبيعة الرقمية للصور الفضائية. ناقشنا في هذا البحث الأساس الرياضي للحكم على الدقة الهندسية للتصحيح الهندسي للصور الفضائية القائم على استخدام نقاط الضبط. وقمنا أيضاً باختبار تأثير طبوغرافية المشهد المصور على هذه الدقة. الاختبار تم بالاستعانة بصور فضائية مقتطعة من المتصفح المجاني Google Earth لمناطق من مدينة اللاذقية في سوريا. كما تم اقتطاع نقاط الضبط من المتصفح نفسه وتحويلها إلى نظام الإحداثيات الستيريوغرافي السوري. أثبتت النتائج أن كثيرات الحدود ثنائية البعد من الدرجة الثانية مناسبة جداً للمشاهد المستوية قليلة الاتساع والتي تكون نقاط الضبط فيها موزعة بشكل موحد على كامل المشهد. The geometric correction of remote sensing images becomes a key issue in production and updating digital maps, multisource data integration, management and analysis for many geomatic applications. 2D polynomial functions are the most prevalent to achieve this correction. Previous researches have shown that the application of 2D polynomials is conditioned by the planarity of the terrain and the uniform distribution of ground control points, but did not explicitly discuss the criteria for evaluating the success or failure of their application. In this study, we will try to give some of these criteria and to develop some old analog cartographic rules to suit the nature of the digital satellite images. In this research, we discussed mathematical foundation for evaluating the precision of control points- based geometric correction of satellite images. We have also tested the effect of the topography of the imaged scene on this accuracy. The test has been carried out by the use of satellite images extracted from Google Earth. These images cover some areas in the city of Latakia in Syria. Also, control points have been extracted from Google Earth and transformed into the Syrian stereographic coordinates system. Results demonstrated that the second degree 2D polynomial is very suitable for plan small scenes with uniform distribution of the control points over the entire scene.